Evaluation of HDDV Emissions Along the East African Northern Corridor (Uganda): Insights From COPERT and ARIMA Models - Tony Kagimu Kawooya; Richard Kimilu; Alex Aganda; James Nyang’aya (Journal of Engineering)
Heavy-duty diesel vehicles (HDDVs), though few in number, are major polluters in East Africa, producing significant amounts of CO2, CO NOx, PM, and PM10. Their rising numbers along the bustling northern corridor, fueled by economic activity, raise concerns. This paper provides an in-depth analysis of the emission trends and projections of HDDVs along the northern corridor, employing the COPERT model for emission estimations from 2015 to 2020 and the ARIMA model for emission predictions from 2021 to 2030. Through detailed analysis, the research illustrates the dynamics of emissions across different vehicle categories: rigid trucks (14–32 t) and articulated trucks (14–60 t), noting the effectiveness of emission control technologies and the impact of evolving emission standards from EURO I to EURO II. A significant finding is the potential advancements in reducing particulate matter emissions per vehicle by up to 20%, contrasting with the rising trends in CO2 emissions of 344% (80.62 to 357.81 kt) that pose challenges for climate change mitigation efforts. Forecasting using the ARIMA model reveals an anticipated significant decline in total emissions from 2021 to 2030 by up to 30%, suggesting a positive outlook toward achieving lower pollution levels through adherence to stricter emission standards and the adoption of cleaner technologies. The paper also addresses the inherent uncertainties in emission estimates, advocating the development of adaptable and resilient environmental policies to effectively respond to a wide range of emission scenarios. This study contributes valuable information on the environmental and public health implications of HDDV emissions, offering a comprehensive understanding that can inform policymaking and technological advancements in the search for sustainable transportation solutions.